Correlation of Blood Glucose Levels with Profiles Hematology on Patient Diabetes Mellitus with Ulcer Diabetes - Candra Kusuma Negara; Tintin Sukartini; Yulis Setiya Dewi; Nursalam; Endang Pertiwiwati; Lucia Andi Chrismilasari; Rifda Nur Achriyana Arif; Devi Rahmayanti; Irfan Maulana (Iranian Journal of Nursing and Midwifery Research)
Background: Diabetes Mellitus (DM) is a metabolic disorder that often leads to diabetic ulcers and persistent hyperglycemia. This condition can cause vascular and metabolic abnormalities, affecting bone marrow performance and altering the hematological profile of patients. This study investigates the correlation between blood glucose levels and hematological profiles in DM patients with diabetic ulcers. Materials and Methods: A quantitative, experimental laboratory study was conducted with 30 blood samples from DM patients at Ulin Hospital Banjarmasin, Indonesia, in February 2023, using purposive sampling. Hematological profiles were analyzed with an automatic hematology analyzer, while blood glucose levels were measured using Point-of-Care Testing (POCT). The Erythrocyte Sedimentation Rate (ESR) was assessed by the Westergren method. Pearson and Spearman coefficients were used to compare ESR results at different intervals, and a regression equation was derived to predict conventional ESR values from micro ESR results. Statistical analysis was performed using multiple correlation regression. Results: The correlation analysis revealed significant relationships between blood glucose and hematological parameters: hemoglobin (p = 0.013), hematocrit (p = 0.011), Mean Corpuscular Volume (MCV) (p = 0.044), and Mean Corpuscular Hemoglobin (MCH) (p = 0.152). No significant correlation was found between blood glucose and the number of erythrocytes (p = 0.997), Mean Corpuscular Hemoglobin Concentration (MCHC) (p = 0.152), total leukocytes (p = 0.082), or platelet count (p = 0.484). Conclusions: A moderate correlation (r = 0.422) was observed between blood glucose levels and the hematological profile in DM patients with diabetic ulcers.